Analysis of domestic legal framework based on international law towards children’s environmental protection - Maizatun Mustafa; Zuraini Ab. Hamid; Kwan, Soo Chen; Mazrura Sahani (Penerbit Universiti Kebangsaan Malaysia, 2021)
Environmental damage and climate change consequences are affecting the health and well-being of many people throughout the world. However as compared to adults, children are more susceptible to environmental hazards because of their unique physiological, developmental and metabolic needs causing them to face a greater risk if exposed to pollution. While imperative actions are persistently being taken by countries globally to address environmental and climate change concerns, confronting these issues in the era of COVID-19 could be more complex due to implications and unprecedented challenges associated with the pandemic. In relation to children, while they are not a category at risk from a medical viewpoint, they are nevertheless not standing on an equal footing in facing environmental consequences of the pandemic effects. In responding to the interlinkages of COVID-19 crisis, environmental degradation, and children’s protection, the article examines provisions of the Child Act 2001 which is the most important legislation in Malaysia on children. The article then examines related policies and international law which provide the foundation of the objectives of the Act. It is imperative that, during the time when new threats to children’s wellbeing keep occurring, policies and international law principles are revisited and comprehended to support the law in securing protective actions for children and in constructing a new normal for the purpose of sustainability.